Isolation of Intestinal Parasites of Public Health Importance from Cockroaches (Blattella germanica) in Jimma Town, Southwestern Ethiopia - Haji Hamu; Serkadis Debalke; Endalew Zemene; Belay Birlie; Zeleke Mekonnen; Delenasaw Yewhalaw (Journal of Parasitology Research)
Cockroaches are claimed to be mechanical transmitters of disease causing microorganisms such as intestinal parasites, bacteria, fungi, and viruses. This study assessed the potential of the German cockroach Blattella germanica in the mechanical transmission of intestinal parasites of public health importance. A total of 2010 cockroaches were collected from 404 households in Jimma Town, southwestern Ethiopia. All the collected cockroaches were identified to species as B. germanica. The contents of their gut and external body parts were examined for the presence of intestinal parasites. Overall, 152 (75.6%) of the 210 batches were found to harbor at least one species of human intestinal parasite. Ascaris lumbricoides, Trichuris trichiura, Taenia spp, Strongyloides-like parasite, Entamoeba histolytica/dispar/moshkovski, Giardia duodenalis and Balantidium coli were detected from gut contents. Moreover, parasites were also isolated from the external surface in 22 (10.95%) of the batches. There was significant difference in parasite carriage rate of the cockroaches among the study sites (P=0.013). In conclusion, B. germanica was found to harbor intestinal parasites of public health importance. Hence, awareness on the potential role of cockroaches in the mechanical transmission of human intestinal parasites needs to be created. Moreover, further identification of the Strongyloides-like worm is required using molecular diagnostics.